Leaf absorption of mineral nutrients in carnivorous plants stimulates root nutrient uptake - Adamec, Lubomír (The New phytologist, 2002)
• The mineral nutrition of terrestrial carnivorous plants was investigated under glasshouse conditions to elucidate ecophysiological adaptations of this plant group. • In Drosera capillaris and D. capensis, absorption of N, P, K, and Mg from insects was relatively efficient (> 43%), whereas that of Ca was not. Carnivorous plants (D. capensis, D. peltata, D. scorpioides, and Dionaea muscipula) exhibited a high efficiency of re-utilization of N (70-82%), P (51-92%), and K (41-99%) from senescing leaves. Re-utilization of Mg was low or negative, and that of Ca highly negative. • In a growth experiment, foliar nutrient supply led to markedly increased growth and nutrient accumulation in D. capillaris, D. aliciae, and D. spathulata. In all the three species tested it was demonstrated that leaf-supplied nutrients were accumulated in the plant biomass and even stimulated root nutrient uptake. • These results suggest that the main physiological effect of leaf nutrient absorption from prey is a stimulation of root nutrient uptake.
Keywords: utilization of prey; terrestrial carnivorous plants; stimulation of root nutrient uptake; leaf nutrient supply; mineral nutrient re-utilization